Sm2O3-induced superconductivity enhancements in bulk Y-123 ceramics synthesized via a novel modified thermal decomposition method - Mohamed Arebat, Ryad Alhadei; Awang Kechik, Mohd Mustafa; Hong, Yap Siew; Kien, Chen Soo; Pah, Lim Kean; Baqiah, Hussien; Barood, Fatma; Humaidi, Syahrul; Peh, Hoo Keong; Shaari, Abdul Halim; Shabdin, Muhammad Kashfi; Miryala, Muralidhar (Elsevier Editora, 2025)
This study presents a novel modified thermal decomposition (MTD) technique for the synthesis of bulk YBa2Cu3O7-δ (Y-123) ceramics with varying samarium oxide (Sm2O3) additions (0.0,0.1,0.3,0.5, 1.0 and 5.0 wt%) under ambient conditions. A structural analysis via X-ray diffraction (XRD) with Rietveld refinement confirmed the dominant formation of the orthorhombic Y-123 phase, accompanied by minor secondary phases, such as Y2BaCuO5 (Y-211) and BaCuO2. Notably, at 0.1 wt% Sm2O3, a distinct Sm1.15Ba1.85Cu3O7 (Sm-123) phase emerged, contributing to enhanced phase stability and effective flux pinning. The optimized 0.1 wt% sample exhibited the highest oxygen content (∼6.87), largest crystallite size (∼1865 Å), and lowest lattice strain, factors directly linked to enhanced superconducting properties. Field emission scanning electron microscopy (FESEM) revealed significant grain growth (∼8.14 μm) and enhanced grain connectivity at 0.1 wt%, while higher doping levels caused porosity and microstructural deterioration. High-resolution imaging further revealed zigzag grain boundaries and nanoscale inclusions acting as flux pinning centers. Energy-dispersive X-ray spectroscopy (EDX) confirmed the uniform elemental distribution and successful Sm incorporation. The 0.1 wt% Sm2O3-added sample achieved the highest critical current density (J c = 5.62 kA/cm2 at 77 K), with a narrow superconducting transition width (Δ T c ≈ 2.96 K), a T c-onset of 92.21 K, and a T c-zero of 89.25 K, indicating minimal weak-link behavior. These findings demonstrate that low-level Sm2O3 addition effectively introduces flux pinning centers while preserving crystal integrity and oxygen stoichiometry. The resulting enhancement in superconducting performance underscores the scalability and efficacy of the MTD route for producing high-performance Y-123 ceramics.